Zmiana jako metaproces organizacji procesowej - Osbert-Pociecha, Grażyna (Change as a Metaprocess in Process-Oriented Organizations, 2009)
The author of the article emphasizes the fact that nowadays change has become a very important factor for both operating and developing of an organization. Change has a special status in organizations, it is a metaprocess. This article also tries to answer the following question: does a process-oriented organization create a good environment for implementation of necessary changes in business processes in firms? (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 413-423